You can put this solution on YOUR website!
It is not real clear what you are asking but I have a feeling you were given a solution set of x =6 and -1 and were asked to form a quadratic equation from this solution set...So we must work backward remember a quadratic equation takes the form of
and when factored each factor is set to zero and the solution is found. In this case we are working backward
so....x=6...in order to make x term = to zero we must subtract 6 so x-6=0....now for x=-1 we must add 1......and get x+1=0 now these two terms can be multiplied together and set equal to zero
(x-6)(x+1)=0--->now multiply this out using foil
combine like terms
is our quadratic equation
If this doesnt answer your question you will have to re write your question and make it more clear....